Microbial Quality of Chhoyla and Kachela: Traditional Newari Meat Products - Khanal, Santosh; Kumal, Asmita; Shrestha, Roshan; Sapkota, Santosh; Baral, Soyuz; K.C, Sudeep; Joshi, Dev Raj (Journal of Food Science and Technology Nepal, 2020)
Chhoyla and Kachela are indigenous and popular meat dishes in the Newar community that are widely consumed in Kathmandu valley. The present study was carried out to investigate the microbial quality of Chhoyla and Kachela from different parts of the valley. The mean total aerobic plate count of Chhoyla and Kachela ranged up to 6.38 and 6.54 log10 cfu/g respectively. The mean total coliform count of Chhoyla and Kachela ranged up to 5.25 and 5.82 log10 cfu/g respectively. Coliform (93%), Staphylococcus aureus (75%), Salmonella Typhi (12%), Salmonella Paratyphi A (5%) and Shigella spp (3%) were isolated from Chhoyla. Likewise, bacteria isolated from Kachela were coliforms (97%), Staphylococcus aureus (86.66%), Salmonella Typhi (15%), Salmonella Paratyphi A (8%) and Shigella spp (7%). High microbial load and the potent human pathogens isolated from these meat products indicate potential risk of food borne diseases.